Overexpression of PD‐L1 in gingival basal keratinocytes reduces periodontal inflammation in a ligature‐induced periodontitis model. Issue 1 (5th June 2021) - Wongtim, Keeratika; Ikeda, Eri; Ohno, Tatsukuni; Nagai, Shigenori; Okuhara, Shigeru; Kure, Keitetsu; Azuma, Miyuki
Abstract: Background: The immune checkpoint programmed cell death 1 (PD‐1): PD‐1 ligand 1 (PD‐L1) pathway plays a crucial role in maintaining immune tolerance and preventing tissue damages by excessive immune responses. PD‐L1 is physiologically expressed and upregulated in keratinocytes (KCs) in the oral cavity. We here investigated the contribution of PD‐L1 that was overexpressed in gingival basal KCs in a ligature‐induced periodontitis model. Methods: Wild‐type (WT) BALB/c and K14/PD‐L1 transgenic (tg) mice, in which PD‐L1 was overexpressed in basal KCs under control of the keratin 14 promoter, were used. To induce periodontitis, a 9‐0 silk ligature was placed around the upper right second molar, and lipopolysaccharide from Porphyromonas gingivalis was applied on the suture. Gingival tissues were collected on day 7, after which histological analyses were performed, including by hematoxylin and eosin and tartrate‐resistant acid phosphate staining (TRAP) and quantitative PCR for proinflammatory cytokines and bone metabolism‐related genes. Alveolar bone loss at 7 weeks after ligature placement was assessed by micro‐computed tomography analysis. Results: PD‐L1 was overexpressed in the basal KCs of all gingival epithelia in K14/PD‐L1tg mice. Early ligature‐induced periodontal inflammation, as assessed based on histological changes, elevation of proinflammatory cytokine (IL‐1β, IL‐6, TNF‐α) expression, periodontal ligament degeneration, and osteoclastogenesis as assessed by Rankl and Opg expression and TRAP+ cells, was markedly impaired in K14/PD‐L1tg mice. Alveolar bone resorption at a late time point was also clearly minimized in K14/PD‐L1tg mice. Conclusion: Overexpression of PD‐L1 in gingival basal keratinocytes in K14/PD‐L1tg mice reduces periodontal inflammation and alveolar bone resorption in a ligature‐induced periodontitis model.